Expression of a recombinant DNA gene coding for the vesicular stomatitis virus nucleocapsid protein. - Sprague, J (1983)
A cDNA clone containing the entire vesicular stomatitis virus nucleocapsid gene was assembled by fusing portions of two partial clones. When the cDNA clone was inserted into a new general-purpose eucaryotic expression vector and introduced into appropriate host cells, abundant N-protein synthesis ensued. The expressed protein was indistinguishable from authentic N protein produced during vesicular stomatitis virus infections. The recombinant N protein was recognized by a polyclonal antibody and two different monoclonal antibodies and could not be resolved by sodium dodecyl sulfate-polyacrylamide gel electrophoresis from authentic N. Our results suggest that the recombinant N protein produced in transfected cells rapidly aggregates into high-molecular-weight complexes in the absence of vesicular stomatitis virus genomic RNA.